2002
DOI: 10.1016/s0011-9164(02)00544-1
|View full text |Cite
|
Sign up to set email alerts
|

Particle interactions and removal of trace contaminants from water and wastewaters

Abstract: The adsorption of trace contaminants on natural particles is of great interest as this adsorption enhances the possibility of removing these with low pressure filtration such as MF and UF. This study shows that natural hormones such as estrone and estradiol will adsorb to natural particles both organic and inorganic. Experiments have shown that the adsorption capacity of organics is a factor of 10 higher than for inorganics. Ultrafiltration of a solution containing NOM and estrone also indicated this adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 11 publications
3
34
0
Order By: Relevance
“…Lai et al (5) observed increasing sorption onto river sediments with 0.3-3.3% organic carbon but also some 40% removal of estrogens sorbed to pure iron oxide, presumably through ion exchange between the surface hydroxyl group on the oxide and the polar phenolic steroids. Similar, although lower, sorption was observed by Schäfer et al (38) for E1 onto hematite and clays in the presence of natural organic matter. The influent to the enhanced primary STP, unlike the advanced STP, is pre-dosed with FeCl 2 upstream in the sewerage system to control sulfide odours before reaching the plant.…”
Section: Steroid Estrogen Concentration and Behaviour Within The Advasupporting
confidence: 86%
“…Lai et al (5) observed increasing sorption onto river sediments with 0.3-3.3% organic carbon but also some 40% removal of estrogens sorbed to pure iron oxide, presumably through ion exchange between the surface hydroxyl group on the oxide and the polar phenolic steroids. Similar, although lower, sorption was observed by Schäfer et al (38) for E1 onto hematite and clays in the presence of natural organic matter. The influent to the enhanced primary STP, unlike the advanced STP, is pre-dosed with FeCl 2 upstream in the sewerage system to control sulfide odours before reaching the plant.…”
Section: Steroid Estrogen Concentration and Behaviour Within The Advasupporting
confidence: 86%
“…The partitioning of the compounds between the aqueous and solid phase was assumed to follow a linear isotherm with finite transfer rate as demonstrated by Schafer et al (2002). The result represented in Figs.…”
Section: Sorption Isotherms Of E2 and Ee2mentioning
confidence: 99%
“…Removal is also effective when the xenobiotic adsorbs on the biomass suspended solids [59,60] and is later separated from the treated water by MF or UF. Adsorption on the sludge is found to be the highest at lower pH where there is less charge repulsion between the sludge and the xenobiotics [117,81]. Removal is also enhanced for xenobiotics with lower dipole moment or higher hydrophobicity [13,54].…”
Section: Xenobiotics Removal Using Membrane Bioreactorsmentioning
confidence: 96%
“…However studies show the occurrence of adsorption by some of the membrane polymers [117] leading to apparent high retention.…”
Section: Xenobiotics Removal By Mf and Ufmentioning
confidence: 99%
See 1 more Smart Citation